Near-Infrared Fluorescence Imaging of Breast Cancer and Axillary Lymph Nodes After Intravenous Injection of Free Indocyanine Green - Bourgeois, Pierre; Veys, Isabelle; Noterman, Danielle; De Neubourg, Filip; Chintinne, Marie; Vankerckhove, Sophie; Nogaret, Jean-Marie (Frontiers in Oncology, 2021)
Background: Near-infrared fluorescence imaging (NIRFI) of breast cancer (BC) after the intravenous (IV) injection of free indocyanine green (fICG) has been reported to be feasible. However, some questions remained unclarified. Objective: To evaluate the distribution of fICG in BC and the axillary lymph nodes (LNs) of women undergoing surgery with complete axillary LN dissection (CALND) and/or selective lymphadenectomy (SLN) of sentinel LNs (NCT no. 01993576 and NCT no. 02027818). Methods: An intravenous injection of fICG (0.25 mg/kg) was administered to one series of 20 women undergoing treatment with mastectomy, the day before surgery in 5 (group 1) and immediately before surgery in 15 (group 2: tumor localization, 25; and pN+ CALND, 4) as well as to another series of 20 women undergoing treatment with tumorectomy (group 3). A dedicated NIR camera was used for ex vivo fluorescence imaging of the 45 BC lesions and the LNs. Results: In group 1, 2 of the 4 BC lesions and one large pN+ LN exhibited fluorescence. In contrast, 24 of the 25 tumors in group 2 and all of the tumors in group 3 were fluorescent. The sentinel LNs were all fluorescent, as well as some of the LNs in all CALND specimens. Metastatic cells were found in the fluorescent LNs of the pN+ cases. Fluorescent BC lesions could be identified ex vivo on the surface of the lumpectomy specimen in 14 of 19 cases. Conclusions: When fICG is injected intravenously just before surgery, BC can be detected using NIRFI with high sensitivity, with metastatic axillary LNs also showing fluorescence. Such a technical approach seems promising in the management of BC and merits further investigation.